Students’ Perceptions toward Using YouTube in EFL Classrooms - Sakkir, Geminastiti; Dollah, Syarifuddin; Ahmad, Jamaluddin (Yayasan Ahmar Cendekia Indonesia, 2020)
The using of videos from YouTube channel in the EFL classroom is imperative to fill the educational needs of the younger generation. Although resources from textbook have remained the standard for centuries, currently, with the fast pace of the development of technology, the usage of YouTube videos in teaching and learning has become a trend. There are a few studies conducted on students’ perceptions of using YouTube to learn the English language. The objective of this research was to investigate the students’ perceptions on the use of YouTube in learning English process at English Education Department, Universitas Negeri Makassar Indonesia. Data were collected using a questionnaire that collected background information of participants and a five-point Likert scale to gauge the students’ perception use of the YouTube in EFL classroom. Findings from this research indicate that the majority of students showed a positive perception toward and a willingness to use YouTube in the EFL classroom. It was also discovered that the students have used YouTube to help them completed their course assignments and study tasks. Hence, it can be concluded that the students preferred to use English YouTube videos to help them enhance their English language level proficiency.